Sistema de Alagados Construídos: framework para elaboração de projetos para performance na prestação de serviços ecossistêmicos - Appleyard, Maria Gabriela Cunha (2024)
Natural Wetland Systems are natural ecosystems with a high degree of adaptation as it is at the interface between the terrestrial and aquatic environment that they make their maximum ecological contribution, housing a diversity of fauna and flora species in their space, helping to maintain biodiversity (SALATI , 1998). Rachel de Queiroz Park is the first project, at municipal level, that implemented a Constructed Wetland (CW) as a way of enabling the rehabilitation of a water body (Cachoeirinha Stream), through environmental strategies that minimize damage caused by pollution. diffuse as well as of domestic origin, favor the supply of Ecosystem Services (ES) for the region. Although the proposal presents relevant methods in the development of landscape projects, a procedural framework for CW projects allows a new perspective when proposing new landscape projects, facilitating the gathering and combination of layers of information, facilitating the visualization of results. Its use allows the designer to obtain answers through the conscious choice of propositional criteria for the project.